TRENDS AND PATTERNS OF RESEARCH ON FINANCIAL LITERACY OF CREATIVE WORKERS IN ARTS AND CREATIVE MSMEs: BIBLIOMETRIC ANALYSIS: TREN DAN POLA PENELITIAN LITERASI KEUANGAN CREATIVE WORKERS PADA UMKM SENI DAN KREASI: ANALISIS BIBLIOMETRIK - Saputri, Dina Wahyu; Yuhertiana, Indrawati (SEGMEN Jurnal Manajemen dan Bisnis, 2025)
This research was conducted to understand how the financial literacy of creative workers in art and creation MSMEs has been discussed in articles. The research method used a database from Google Scholar from 2020-2024. After filtering, there were 174 articles that matched the keywords processed using Publish or Perish and VOSviewer. Some of the articles discuss how important financial literacy is for managing finances in the future.The results of this study show that there are four groups of articles. These articles explain the relationship between financial attitudes and behavior. They also reflect the integration of financial knowledge and technology. Some articles emphasize strategies for proper financial management. Others emphasize effective financial behavior in realizing maximum financial performance. Finally, some emphasize that effective creative workers are key elements in realizing good financial literacy. We hope that this research will be a useful resource for future studies related to financial literacy in arts and creative small businesses.